Speech Act of Pragmatic - Novia Widyasari Rahayu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
ABSTRACT When a speaker says anything, there are specific goals beyond the words or phrases. This is an aspect of pragmatics. The activity performed by generated utterances is referred to as speech actions. Saying something can be used to perform an action. Speech actions allow the speaker to portray physical activity using just words and phrases. The acts taken are mostly determined by the words spoken. There are several things to consider when it comes to English as a foreign language. If utterances are delivered in the mother language, it is simple for speakers or listeners to figure out what they imply.